The Influence of Digital Influencers on Buying Interest in E-Commerce Tiktok Shop - Ulfa, Azzahra; Hsb, Saima Putri; Mauliana, Tiara Friska; Pradana, Farhan; Adnan, Hafizur Kahfi; Harahap, Nursapiah (Universitas Ibn Khaldun, 2024)
The digital era has changed the way consumers interact with products and services, with e-commerce becoming one of the main platforms used by customers to shop online, with e-commerce becoming of the main platforms used by customers to shop online. In this context, the role of digital influencers as key drivers in shaping consumer preferences and shopping behavior is increasingly receiving significant attention. TikTok, a social media platform that is experiencing rapid growth, has introduced an e-commerce feature known as TikTok Shop. This research was created to find out the role and influence of digital influencers in shaping consumer buying interest in the e-commerce TikTok Shop. This research uses quantitative methods with a descriptive approach.